Professional Care Providers Instruction: Does It Reduce Postoperative Fever Rate? - Pramudya, Indradi; Youandi, Abdi Agus; Indriani, Wiwin (Jurnal Kedokteran Brawijaya)
Postoperative fever is a fever that occurs after surgery and might develop among children, adults, and the elderly indirectly related to the type of surgery. Surgical site infection (SSI) is the most common cause of postoperative fever. However, it is common that the specific causes of fever are not found or without any signs of infection. This study aimed to determine the cause of postoperative fever and its intervention plan. This research was a case study at X Hospital in September to October 2019 initiated by identifying the root of the problem, identifying the priority of the root problem, and planning the intervention. The results of the identification of the root of the problems found that fever occurred less than 24 hours postoperatively. The results of the root problem identification revealed no SOP that regulates the Professional Care Providers (PCP) to give instructions to patients if there is a delay in the operating schedule. The proposed intervention plan is to make regulations regarding service delay instructions. Postoperative fever less that is than 24 hours causes patient discomfort due to the absence of instructions from the PCP if there is a delay in the operating schedule. The establishment of the regulations is a solution to reduce the incidence of postoperative fever.Keywords: postoperative fever, operation delay, regulation